Benefits of Mindfulness Training for Patients With Progressive Cognitive Decline and Their Caregivers. (May 2015) - Paller, Ken A.; Creery, Jessica D.; Florczak, Susan M.; Weintraub, Sandra; Mesulam, M.-Marsel; Reber, Paul J.; Kiragu, Jessica; Rooks, Joshua; Safron, Adam; Morhardt, Darby; O'Hara, Mary; Gigler, Kathryn L.; et al.
New strategies are needed to help people cope with the repercussions of neurodegenerative disorders such as Alzheimer's disease. Patients and caregivers face different challenges, but here we investigated an intervention tailored for this combined population. The program focused on training skills such as attending to the present moment nonjudgmentally, which may help reduce maladaptive emotional responses. Patients participated together with caregivers in weekly group sessions over 8 weeks. An assessment battery was individually administered before and after the program. Pre–post analyses revealed several benefits, including increased quality-of-life ratings, fewer depressive symptoms, and better subjective sleep quality. In addition, participants indicated that they were grateful for the opportunity to learn to apply mindfulness skills and that they would recommend the program to others. In conclusion, mindfulness training can be beneficial for patients and their caregivers, it can be delivered at low cost to combined groups, and it is worthy of further investigation.